Peningkatan Hasil Belajar Matematika Materi Mengurutkan Bilanagn Melalui Model Pembelajaran Problem Based Learning - Pratiwi, Widya Ayu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study was to determine the increase in student learning outcomes in the first semester of mathematics lessons in elementary school class I on the material of sorting numbers through the Problem Based Learning learning model. The subjects of this study were the first grade students of SD Negeri Pasucen 02 for the 2020/2021 academic year, totaling 26 students. The research conducted was classroom action research (CAR) consisting of two cycles, namely cycle I and cycle II. The stages of each cycle are planning, implementation, observation and reflection. Each cycle consists of two meetings. Data collection was obtained from the results of tests and observations. While the data analysis includes qualitative data and quantitative data. In the first cycle, the classical completeness was 61.84%. While in the second cycle of 85,00%. These results indicate that the Problem Based Learning model can improve the learning outcomes of class I students at SD Negeri Pasucen 02 in the content of learning mathematics in the matter of sorting numbers.